Uvod v retoriko za turistične delavce: Delovni listi - Potočnik Topler, Jasna (2017)
Introduction to Rhetoric for Tourism Workers: Worksheets. Rhetoric is the art of persuasion. For thousands of years, people have praised and studied it. However, the foundations of rhetorical theory were laid by the Ancient Greek Philosopher Aristotle. Throughout history, rhetoric experienced development, ascents, as well as falls. Today, we are increasingly aware of the significance of mastering this skill in a wide variety of areas of public and private lives, since it contributes to better reading literacy of the individual and society as a whole. One of the goals of teaching rhetoric at the Faculty of Tourism of the University of Maribor is to prepare the students for analysis, and more precise and accurate formulation of arguments and persuasive techniques in their everyday lives: From private conversations, through media, study situations, and the writing of professional texts. It is also intended to acquaint students with various discourses, to teach them independent, self-confident, clear, structured and critical expression of their opinions, and the formation of well structured shorter and longer texts. The booklet contains worksheets that are meant as a guide to introducing rhetoric for tourism professionals, with topics such as history, rhetorical genres, canons, persuasion and language at the forefront.
Keywords: retorika; prepričevanje; govor; argument; nastop